Force Equalization Control of Redundant Electromechanical Actuation System by FOPID and Current Feedforward - Jianzhong Yang; Dong Hou; Xiaozhe Sun; Jinpeng Zuo (IEEE Access, 2023)
To solve force-fight problem of the fly-by-wire redundant electromechanical actuation system(EMAs) in an active-active mode, a force equalization control method with feedforward and feedback control is proposed. Aiming at the un-ideal stability and robust performance of force equalization controller, an optimized Fractional Order PID controller with current feedforward (FO+IF)is adopted. Aiming at the limitation of traditional parameter tuning, the controller parameters are optimized iteratively using the particle swarm optimization (PSO) algorithm. To improve the anti-interference performance of the system, a state observer for load torque is introduced into the current feedforward control. Through setting a serious force fight situation with multiple disturbances, the performance of FOPID and FO+IF on force fight and position response were compared, and the robustness of the system under the influence of sensitive parameters was analyzed by Monte Carlo method. The experimental results show that FO+IF can effectively improve the impact of static force fight and dynamic force fight on the system.